2022
DOI: 10.33474/j-reall.v3i2.16504
|View full text |Cite
|
Sign up to set email alerts
|

Subscribing to diverse subjects in different classes: language development dichotomy

Abstract: Language teachers, yet on the other side, language enhancement is compromised for learners whose home language is not English. Further than that, for teachers lacking specialisation of other subjects allocated to them, besides English language teaching and learning becomes a monotonous activity that does not inspire learner attitudes more so that the greatest percentage of subjects underpinning the curriculum is offered in an English medium. This paper aims to explore if offering different subjects in varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…The findings of this study reveal that M‐SGTs can successfully transition to become English teachers without formal teacher preparation. This finding matches that of Makena and Omodan (2022) but contrasts with that of Goos et al (2020) and Crisan and Rodd (2014). The finding suggests that M‐SGTs have the capacity to develop their identity and expertise in EFL teaching even without specific training in that subject area.…”
Section: Findings and Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The findings of this study reveal that M‐SGTs can successfully transition to become English teachers without formal teacher preparation. This finding matches that of Makena and Omodan (2022) but contrasts with that of Goos et al (2020) and Crisan and Rodd (2014). The finding suggests that M‐SGTs have the capacity to develop their identity and expertise in EFL teaching even without specific training in that subject area.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…In contrast, Izquierdo et al's (2021) study suggested that M-SGTs simplify their instructional approaches by avoiding textbooks and using simple supplementary texts. Another study by Makena and Omodan (2022) reported that the English instructional methodologies employed by comparable M-SGTs undermine student learning, whereas the present study found that M-SGTs engage in more interactive EFL teaching by utilising inclusive materials and supplementary texts.…”
Section: M-sgt-6 Emphasisescontrasting
confidence: 80%
See 3 more Smart Citations